2008
DOI: 10.1177/0013164408315266
|View full text |Cite
|
Sign up to set email alerts
|

Effect Size Reporting Practices in Published Articles

Abstract: Effect size (ES) reporting practices in a sample of 10 educational research journals are examined in this study. Five of these journals explicitly require reporting ES and the other 5 have no such policy. Data were obtained from 99 articles published in the years 2003 and 2004, in which 183 statistical analyses were conducted. Findings indicate no major differences between the two types of journals in terms of ES reporting practices. Different conclusions could be reached based on interpreting ES versus p valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
51
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 33 publications
8
51
1
1
Order By: Relevance
“…See Table 4 for details. This result is consistent with the findings in the previous studies (e.g., Alhija & Levy, 2007;Hutchins & Henson, 2002;Kirk, 1996;McMillan et al, 2002), though Dunleavy et al (2006) found that variance-account-for statistics were typically omitted. The popularity of this type of effect size measure can be explained by the fact that 76% of the 1,243 articles (n ϭ 938) used general linear models as the main NHST method, and 75% of the 610 articles that reported effect size (n ϭ 455) used general linear models (cf.…”
Section: Reporting Effect Sizesupporting
confidence: 92%
“…See Table 4 for details. This result is consistent with the findings in the previous studies (e.g., Alhija & Levy, 2007;Hutchins & Henson, 2002;Kirk, 1996;McMillan et al, 2002), though Dunleavy et al (2006) found that variance-account-for statistics were typically omitted. The popularity of this type of effect size measure can be explained by the fact that 76% of the 1,243 articles (n ϭ 938) used general linear models as the main NHST method, and 75% of the 610 articles that reported effect size (n ϭ 455) used general linear models (cf.…”
Section: Reporting Effect Sizesupporting
confidence: 92%
“…According to the editorial guidelines and methodological recommendations of several prominent educational and psychological journals, it is necessary to include some measures of effect size and confidence intervals for all primary outcomes (Alhija & Levy, 2009;Fritz, Morris & Richler, 2012;Kelley & Preacher, 2012;Odgaard & Fowler, 2010;Peng et al, 2013;Sun, Pan & Wang, 2010). Among the several inadequate effect size reporting and interpretation practices, Alhija and Levy (2009) and Peng et al (2013) especially emphasized that the majority of popular effect size measures are positively biased estimators such as the standardized mean difference index Cohen's d, the strength of association measureη 2 , and the sample squared multiple correlation coefficient R 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, numerous practical guidelines and suggestions for selecting, calculating, and interpreting effect size indices for various types of statistical analyses have been provided in the literature, such as Alhija and Levy (2009), Breaugh (2003), Durlak (2009), Ferguson (2009, Fern and Monroe (1996), Grissom and Kim (2012), Huberty (2002), Kirk (1996), Kline (2004), Olejnik and Algina (2000), Richardson (1996), Rosenthal, Rosnow, and Rubin (2000), Rosnow and Rosenthal (2003), and Vacha-Haase and Thompson (2004). It has steadily become a general consensus in the methodological literature of behavior, education, management, and related disciplines that effect sizes accompanied by their corresponding confidence intervals are perhaps the best approach for conveying quantitative information in applied research.…”
mentioning
confidence: 99%